The modified COVID‐19 Yorkshire Rehabilitation Scale (C19‐YRSm) patient‐reported outcome measure for Long Covid or Post‐COVID‐19 syndrome. Issue 9 (1st June 2022) - Sivan, Manoj; Preston, Nick; Parkin, Amy; Makower, Sophie; Gee, Jeremy; Ross, Denise; Tarrant, Rachel; Davison, Jennifer; Halpin, Stephen; O'Connor, Rory J.; Horton, Mike
Abstract: Background: The C19‐YRS is the literature's first condition‐specific, validated scale for patient assessment and monitoring in Post‐COVID‐19 syndrome (PCS). The 22‐item scale's subscales (scores) are symptom severity (0–100), functional disability (0–50), additional symptoms (0–60), and overall health (0–10). Objectives: This study aimed to test the scale's psychometric properties using Rasch analysis and modify the scale based on analysis findings, emerging information on essential PCS symptoms, and feedback from a working group of patients and professionals. Methods: Data from 370 PCS patients were assessed using a Rasch Measurement Theory framework to test model fit, local dependency, response category functioning, differential item functioning, targeting, reliability, and unidimensionality. The working group undertook iterative changes to the scale based on the psychometric results and including essential symptoms. Results: Symptom severity and functional disability subscales showed good targeting and reliability. Post hoc rescoring suggested that a 4‐point response category structure would be more appropriate than an 11‐point response for both subscales. Symptoms with binary responses were placed in the other symptoms subscale. The overall health single‐item subscale remained unchanged. Conclusion: A 17‐item C19‐YRSm was developed with subscales (scores): symptom severity (0–30), functional disability (0–15), other symptoms (0–25), and overall health (0–10).